OCT-Angiography in Early Choroidal Melanoma and Choroidal Nevi - S. V. Saakyan; E. B. Myakoshina; M. R. Khlgatyan; N. V. Sklyarova (Oftalʹmologiâ)
Purpose: To study the features of small choroidal melanoma and choroidal nevi angioarchitectonics using the optical coherence tomography angiography (OCTA).Patients and methods. We examined 128 patients with small choroidal neoplasms: 41 — with small choroidal melanoma (group 1), 42 — with suspicious nevi (group 2) and 45 — with benign nevi (group 3). All patients underwent general ophthalmic examinations and special instrumental diagnostic methods (ultrasound examination (US), fluorescence angiography (FA), spectral optical coherence tomography (SOCT), OCTA).Results. OCTA in all patients with small choroidal melanoma showed neovascular network under retinal pigment epithelium. We found a looped, cranked-twisted, heterogeneous vascular network with uneven clearance and with numerous bends and weaves, located under the vessels of retina. The limiting avascular zone corresponding to the tumor slope was determined in 19 (46.3 %) of 41 cases. There was a rim of dilated hyperreflective choriocapillaries on the periphery of the tumor. We identified hyperreflective homogeneous enlarged choriocapillaries in the focus area with a brighter glow than the surrounding choriocapillaries in 39 (92.9 %) of 42 patients with suspicious choroidal nevus. We detected an avascular zone with surrounding extended hyperreflective choriocapillaries in the center of the nevus in 3 (7.1 %) of 42 cases. We diagnosed homogeneous isoreflective choriocapillaries similar in brightness to the surrounding vessels in all 45 patients with benign nevi.Conclusions. Thus, the complex of clinical and instrumental methods, including OCTA, makes it possible to establish the diagnosis of malignant tumor of the choroid in early stages. At the same time, OCTA: 1) allows to visualize of the tumor vessels in the choroidal layer in 100 % of cases of in small choroidal melanoma; 2) makes it possible to distinguish the newly formed tumor vessels from the choriocapillaries in case of small choroidal melanoma; 3) provides an opportunity to establish the correct diagnosis and provide timely assistance to patients with benign and malignant choroidal tumors.